Genomic structure, expression pattern, and functional characterization of transcription factor E2F-2 from black tiger shrimp (Penaeus monodon). - Bobo Xie (PLoS ONE, 2017)
Transcription factor E2F-2 is a regulator of cell cycle. Researchers identified E2F-2 genes from yeasts to humans, but few reports investigated E2F-2 gene from black tiger shrimp. In the present study, we cloned E2F-2 gene from black tiger shrimp (Penaeus monodon). Full-length PmE2F-2 complementary DNA sequence measures 3,189 bp with an open reading frame of 1,371 bp. Complete PmE2F-2 genomic sequence (17,305 bp) of P. monodon contains nine exons, which are separated by eight introns. Quantitative real-time polymerase chain reaction (qRT-PCR) analysis indicated that PmE2F-2 is highly expressed in hepatopancreas and ovaries of P. monodon. Highest PmE2F-2 expression levels were observed in stage III ovarian development of P. monodon. PmE2F-2 expression levels were significantly augmented in ovaries of P. monodon after 5-hydroxytryptamine injection and eyestalk ablation. RNA interference experiments were conducted to examine PmE2F-2, PmCDK2, and PmCyclin E expression profiles. PmE2F-2 was successfully knocked down in ovaries and hepatopancreas via double-stranded RNA (dsRNA)-E2F-2 injection. In the same organs, PmE2F-2 expression localization and level were investigated through in situ hybridization, which revealed consistent results with those of qRT-PCR. After dsRNA-E2F-2 injection, gonadosomatic index of shrimp was significantly lower than those following dsRNA-GFP and phosphate-buffered solution injections. Therefore, PmE2F-2 may be involved in ovarian maturation in P. monodon.